JEWISH QUESTION AND THE CREATION OF THE ISRAELI STATE (Annual of the Faculty of Philosophy in Skopje, 2011)
Jews and Jewish questions were a reflection of deep prejudices against Jews, which cannot be overcome even in the modern world. The hatred of Jews in the two-thousand history is carrying out the policy of the villain of the piece. Along with the Jews the term holocaust appears which means fully “extermination'9 or “burning”. After the destruction of the Jewish state in Palestine, the Jews settled throughout the territory of the Roman Empire. Living in many countries, they remained closed as a minority community which adhered to their faith and customs. They had a significant role in the social and economic life in many countries in Europe. That was the cause of the anti-Semitism as a struggle against the Jews as an ethnic community. The German Nazism declared anti-Semitism as official doctrine and state policy in order to exterminate the Jews. At that period the biggest exterminations of Jews were done. The struggle of the Jews for own country ended after the Second World War, when the Jewish state was created.
Keywords: JEWS; PALESTINE; ANTI-SEMITISM; ZIONISM; CONCENTRATION CAMPS